2004
DOI: 10.3201/eid1006.040010
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sources of Prion Transmission in Mule Deer

Abstract: Whether transmission of the chronic wasting disease (CWD) prion among cervids requires direct interaction with infected animals has been unclear. We report that CWD can be transmitted to susceptible animals indirectly, from environments contaminated by excreta or decomposed carcasses. Under experimental conditions, mule deer (Odocoileus hemionus) became infected in two of three paddocks containing naturally infected deer, in two of three paddocks where infected deer carcasses had decomposed in situ ≈1.8 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
372
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(381 citation statements)
references
References 22 publications
9
372
0
Order By: Relevance
“…Given that environmental contamination with CWD prions likely occurs [55], domestic ruminants may be exposed to CWD through common grazing areas. However, sheep and cattle appear to be poorly susceptible to mule deer CWD: ic inoculation with mule deer CWD succeeded to infect only 2 of 8 sheep [28].…”
Section: Interspecies Cwd Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that environmental contamination with CWD prions likely occurs [55], domestic ruminants may be exposed to CWD through common grazing areas. However, sheep and cattle appear to be poorly susceptible to mule deer CWD: ic inoculation with mule deer CWD succeeded to infect only 2 of 8 sheep [28].…”
Section: Interspecies Cwd Transmissionmentioning
confidence: 99%
“…Recently, in a breakthrough finding, saliva from CWD-infected deer was shown to transmit prion disease [50]. An additional experiment by Miller et al showed that CWDinfected carcasses allowed to decay naturally in confined pastures can lead to CWD infections in captive deer, demonstrating the potential for environmental contamination to spread infection [55]. Modelling studies have provided further support that environmental contamination is likely playing a significant role in transmitting CWD [53,56].…”
Section: Disease Control Challenges Posed By Cwdmentioning
confidence: 99%
“…2). Wisconsin has dense white-tailed deer populations (15)(16)(17)(18)(19)(20) deer/km2) with a prevalence of up to 13% of the male deer in some regions [12]. The origins of these recent outbreaks remain under investigation, but in some cases spillover from infected game farms seems a plausible explanation.…”
Section: Epidemiology and Disease Managementmentioning
confidence: 99%
“…This question is arguably one of the biggest conundrums in the CWD field, and hypotheses range from spread via direct contact to exposure through grazing in areas contaminated by prion-infected secretions, excretions (saliva, urine, feces), tissues (placenta), or decomposed carcasses. Indeed, Miller et al have shown that CWD-infected carcasses allowed to decay naturally in confined pastures can lead to CWD infections in captive deer [19]. Perhaps multiple exposure pathways can lead to an infection, nevertheless, horizontal spread of CWD is clearly Inflammation may increase the risk of prion shedding in cervids.…”
mentioning
confidence: 99%
“…When considering the entire TSE disease family, only the cervid specific chronic wasting disease (CWD) and sheep scrapie are readily transmissible to susceptible hosts through horizontal transmission of infected animals or environmental reservoirs of infectivity [6][7][8]. To develop a CWD management tool, we have evaluated peptide-based vaccine candidates for eventual use in farmed and wild cervids.…”
mentioning
confidence: 99%